Troubling Claims of Normalization: Continuing Stigmas within Michigan's Medical Cannabis Community. Issue 9 (2nd September 2022) - Reid, Matt
ABSTRACT: Cannabis has undoubtedly become more accessible and commonplace in American society, and scholars and laypeople commonly claim it has achieved a normalized status. On the other hand, structural and social stigmas still impact medical and non-medical cannabis users' everyday lives. This study attempts to restore nuance to the academic debate on cannabis normalization. The primary method used here is focus groups of cannabis patients in Michigan (n = 21), which are occasionally supplemented by key informant interviews. Findings suggest cannabis patients face persistent cannabis-related stigmas and discrimination, even in a post-prohibition state like Michigan. These stigmas create tension for patients in their personal relationships, work environments, and sense of self. Furthermore, experiences of being a cannabis patient vary along the lines of age, gender, race, and occupational status. As such, this study suggests claims of normalization may be premature or symptomatic of social privileges.